Conflict of Interest in Public Procurement : A Case Study of Indonesia’s Government Institution XYZ - Atika Yanel Fauziah; Marpaung, Jonathan (Fakultas Ekonomi Universitas Kadiri, 2024)
This research aims to analyze the implications of conflicts of interest in procurement activities within Indonesian government institutions, focusing on motives such as personal gain, nepotism, and political influence on Procurement Committees. The study conducted interviews with seven procurement committees in a government institution in Indonesia. The findings indicate that the acceptance of personal gain significantly affects the procurement process, as the authority held by procurement committees provides opportunities to exploit gaps in each procurement process. Additionally, nepotism leads to biased decisions by the procurement committee, resulting in deviations from established procedures. Meanwhile, political influence on procurement committees, both directly and indirectly, poses a risk of intervention that disrupts the procurement process from planning to the determination of winners. Furthermore, based on Cause-Effect Diagram analysis, it was found that factors such as low individual moral principles, suboptimal inherent supervision, and the lack of stringent sanctions against fraudulent actors are the main triggers of conflicts of interest in the procurement process. Proposed improvements include the implementation of moral principles to encourage individuals involved in procurement to prioritize institutional interests and the involvement of internal supervisors in every stage of the procurement process to help identify signs of fraud or